2020
DOI: 10.1097/olq.0000000000001170
|View full text |Cite
|
Sign up to set email alerts
|

Extragenital Gonorrhea and Chlamydia Positivity and the Potential for Missed Extragenital Gonorrhea With Concurrent Urethral Chlamydia Among Men Who Have Sex With Men Attending Sexually Transmitted Disease Clinics—Sexually Transmitted Disease Surveillance Network, 2015–2019

Abstract: Background Extragenital gonorrhea (GC) and chlamydia (CT) are usually asymptomatic and only detected through screening. Ceftriaxone plus azithromycin is the recommended GC treatment; monotherapy (azithromycin or doxycycline) is recommended for CT. In urethral CT-positive/urethral GC-negative persons who are not screened extragenitally, CT monotherapy can lead to GC undertreatment and may foster the development of gonococcal antimicrobial resistance. We assessed urethral and extragenital GC and CT p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 17 publications
4
41
0
Order By: Relevance
“…Many oropharyngeal bacterial STIs such as NG and CT are often asymptomatic [48][49][50][51] and estimates of their prevalence is limited by insufficient testing [52][53][54]. Our overall prevalence of oropharyngeal STIs was 7%, 5% for NG and 2% for CT which is consistent with estimates from higher-income countries.…”
Section: Plos Onesupporting
confidence: 84%
“…Many oropharyngeal bacterial STIs such as NG and CT are often asymptomatic [48][49][50][51] and estimates of their prevalence is limited by insufficient testing [52][53][54]. Our overall prevalence of oropharyngeal STIs was 7%, 5% for NG and 2% for CT which is consistent with estimates from higher-income countries.…”
Section: Plos Onesupporting
confidence: 84%
“…However, many pharyngeal and rectal CT and NG cases go undiagnosed and more importantly untreated because of their asymptomatic nature and lower screening rates 2–6 13–16. Previous studies have demonstrated that screening for urogenital CT/NG alone among MSM may miss a substantial amount (14%–85%) of CT/NG cases 6 13 17–22. In other words, a negative urogenital test for CT/NG may miss positive CT/NG cases at the pharyngeal and rectal sites had urogenital testing alone been performed.…”
Section: Introductionmentioning
confidence: 99%
“…20,25,26 In a study of over 77,000 adult MSM in the Sexually Transmitted Diseases Surveillance Network, 75% of extragenital GC and 89% of extragenital CT infections were associated with negative urethral tests. 23 To our knowledge, our study presents the largest database of co-STIs in AYAs with HIV in the US and provides unique insight into the behaviors and distribution of co-infections in this group, highlighting important implications for screening practices. Because the most frequent presentation of GC and CT in our study was asymptomatic extragenital infection, the majority would have been missed without routine screening at all anatomic sites.…”
Section: Discussionmentioning
confidence: 91%